2016
DOI: 10.1186/s12917-016-0801-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hereditary bisalbuminemia in bottlenose dolphins (Tursiops truncatus, Montagu 1821): comparison between capillary zone and agarose gel electrophoresis

Abstract: BackgroundHereditary bisalbuminemia is a relatively rare anomaly characterized by the occurrence of two albumin fractions on serum protein separation by electrophoresis. In human medicine, it is usually revealed by chance, is not been clearly associated with a specific disease and the causative genetic alteration is a point mutation of human serum albumin gene inherited in an autosomal codominant pattern. This type of alteration is well recognizable by capillary zone electrophoresis (CZE), whilst agarose gel e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Surely, age, sex and pregnancy could be used for partitioning (45, 72), but in marine mammals greater attention should be given to the difference between wild and managed animals. Serum protein electrophoresis values obtained in managed bottlenose dolphins showed lower total proteins and higher albumin levels compared to reference intervals derived from free-ranging (46) while 9 wild-caught manatees, apparently clinically healthy, had SAA level above reference limit (56). These data could indicate a trend to an inflammatory status or the presence of subclinical inflammation in free-ranging animals which are more exposed to immunological stimuli.…”
Section: Acute Phase Protein In Marine Mammals: Challenges and Futurementioning
confidence: 80%
See 1 more Smart Citation
“…Surely, age, sex and pregnancy could be used for partitioning (45, 72), but in marine mammals greater attention should be given to the difference between wild and managed animals. Serum protein electrophoresis values obtained in managed bottlenose dolphins showed lower total proteins and higher albumin levels compared to reference intervals derived from free-ranging (46) while 9 wild-caught manatees, apparently clinically healthy, had SAA level above reference limit (56). These data could indicate a trend to an inflammatory status or the presence of subclinical inflammation in free-ranging animals which are more exposed to immunological stimuli.…”
Section: Acute Phase Protein In Marine Mammals: Challenges and Futurementioning
confidence: 80%
“…The interpretation of total proteins values and electrophoretic pattern of serum proteins is receiving increased attention also in marine mammals in which a typical pathologic pattern could be identified in inflammatory diseases (40). Reference intervals for these markers are available for free-ranging bottlenose dolphins (45) and, compared to these, recently data on managed dolphins showed slightly lower values of TP, α-globulins, and γ-globulins and higher albumin and albumin/globulins ratio (46).…”
Section: Acute Phase Reaction and Acute Phase Protein In Marine Mammalsmentioning
confidence: 99%
“…1,69,74 Differences between AGE and CZE, some of which are substantial, have been demonstrated for the mouse, rat, dog, marmoset, dolphin, cheetah, and cat. 45,48,69,75,76 Additional studies in various reptile species have demonstrated the necessity of method-specific RIs with the use of CZE in Hermann's tortoise, green turtle, red-eared slider, map turtle, panther chameleon, and boa constrictor. 29,47,[77][78][79] Differences in alpha and beta globulins were also reported in the black-headed ibis, chicken, black kite, and racing pigeon.…”
Section: Capillary Zone Electrophoresismentioning
confidence: 99%
“…However, CZE, due to its higher accuracy and easiness of use through automatization, is increasingly replacing AGE as a research and diagnostic tool for PPE analysis in many species including marine animals [ 29 ]. CZE has proven to consistently resolve electrophoretogram protein fractions that are frequently not differentiated by using AGE [ 30 ]. Previous studies evaluating PPE in sharks and rays divided these species’ electrophoretograms into five fractions equivalent to pre-albumin, albumin, alpha-, beta-, and gamma-globulins.…”
Section: Discussionmentioning
confidence: 99%